Numerical study of Unsteady Fluid Flow and Heat Transfer Through a Rotating Curved Rectangular Channel - Islam, Md Zohurul; Arifuzzaman, Md; Mondal, Rabindra Nath (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Numerical study of unsteady fluid flow and heat transfer through a rotating curved rectangular channel with aspect ratio 2 and curvature ratio 0.05 has been performed by using a spectral-based numerical method, and covering a wide range of the rotational parameter, the Taylor number Ta, for both the positive and negative rotation of the channel. In this paper, unsteady flow characteristics are investigated under combined action of the centrifugal, Coriolis and buoyancy forces for the Dean number De = 1000. For positive rotation, we investigated unsteady solutions for 0 ≤Ta ≤500, and it is found that the chaotic flow turns into steady-state flow through periodic or multi-periodic flows. For negative rotation, on the other hand, unsteady solutions are investigated for –500 ≤Ta≤0, and it is found that the unsteady flow undergoes through various flow instabilities. Typical contours of secondary flow patterns and temperature profiles are obtained at several values of Ta, and it is found that the unsteady flow consists of asymmetric two- to eightvortex solutions. The present study shows that convective heat transfer is significantly enhanced as the secondary flow becomes stronger and the chaotic flow enhances heat transfer more effectively than the steady-state or periodic solutions. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 73-92